5x + 3 = 4xSubtract 3 from each side:5x = 4x - 3Subtract 4x from each side:x = -3
-4x +5x +4 =7 x + 4 = 7 x = 3
x=3 That wasn't hard at all. 5x-10=-7+4x -4x -4x _____________ x-10=-7 +10 +10 _____________ x=3
x2 + 4x - 9 = 5x + 3 ∴ x2 - x - 12 = 0 ∴ (x + 3)(x - 4) = 0 ∴ x ∈ {-3, 4}
x2+4x-9 = 5x+3 x2+4x-5x-9-3 = 0 x2-x-12 = 0 (x+3)(x-4) = 0 x = -3 or x = 4
5x - 4x = 13 - 3 ie x = 10
33
5x + 3 = 4xSubtract 3 from each side:5x = 4x - 3Subtract 4x from each side:x = -3
8x + 5x + 2x + 4x = 114 19x = 114 x = 6 then 5x + 3 = 5*6 + 3 = 33
4x - 3 - 5x + 7 = 6 4x - 5x = 3 - 7 + 6 -1x = 2 x = -2
-4x +5x +4 =7 x + 4 = 7 x = 3
5x + 3 - 4 + 4x = 9x -1
x=3 That wasn't hard at all. 5x-10=-7+4x -4x -4x _____________ x-10=-7 +10 +10 _____________ x=3
x2 + 4x - 9 = 5x + 3 ∴ x2 - x - 12 = 0 ∴ (x + 3)(x - 4) = 0 ∴ x ∈ {-3, 4}
x2+4x-9 = 5x+3 x2+4x-5x-9-3 = 0 x2-x-12 = 0 (x+3)(x-4) = 0 x = -3 or x = 4
Then x = 6 Therefore; 5x + 3 = 33 First you have to solve the value of X: 8X + 5X + 2X +4X = 114; OR 19x = 114. When you divide both sides of the equation by 19 to solve for X, you find that X = 6. Ergo, 5X + 3 = 30 + 3 = 33; hence, 5X + 3 = 33.
x + 3 + 4x = 13 3 +5x = 13 -- combine like terms 5x = 10 -- subtract 3 x = 2 --- divide by 5 "x" equals two